The Role Of The Department Of Transportation In Improving The Quality Of City Transportation Services ( Study At The Transportation Service Of Medan City) - Mora Rizki Hasibuan (IHSA Institute, 2020)
City transportation is one of the modes of public transportation commonly used by people in urban areas, urban transportation is provided to transport passengers to certain destinations according to predetermined routes. In terms of service quality, urban communities prefer private transportation or private transportation to fulfill their mobility. This study tries to explain the role of the Medan city transportation service in improving the quality of service, the Medan city transportation service is an implementing element of the Medan City government in the field of transportation which is led by a head of service and is responsible to the regional head through the regional secretary. From the results of this study, it can be seen that the Medan City Transportation Service has a very important role in improving the quality of city transportation services. the Medan city transportation service as a facilitator in the field of public services and a facilitator in the field of urban transportation infrastructure, the Medan city transportation service as the executor of development, and the transportation service as controlling or supervising related to improving the quality of urban transportation services.